Penerapan Metode Naïve Bayes Dalam Mendiagnosa Penyakit Leptospirosis - Rima Tamara Aldisa; Sechan Alfarisi; Mohammad Aldinugroho Abdullah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
There are still many people who are less concerned with environmental cleanliness, where this can lead to the accumulation of bad bacteria that cause disease. One of them is Leptospirosis, a disease caused by a bacterial infection, namely the Leptospira strain. Leptospirosis is a disease caused by the laying of bacteria in animals that is transmitted to humans. This disease is often ignored by the public due to lack of understanding about this disease and the high cost of conducting examinations and consulting a doctor or hospital. So that in overcoming this we need a way that is able to help the community in knowing and diagnosing Leptospirosis, one of which is by using an expert system. The expert system used in solving the problem of Leptospirosis is by using the Naïve Bayes method. The application of the Naïve Bayes method in diagnosing Leptospirosis is carried out by collecting data about Leptospirosis where this process aims to find out what symptoms are caused by Leptospirosis. The process of collecting data on this disease is done by interviewing an expert or doctor who handles the problem of Leptospirosis. The results of the diagnosis of Leptospirosis based on the calculation of the Naïve Bayes method with new user data samples get results with a definite level of accuracy where the user experiences Leptospirosis disease with mild symptoms of 63% and the results of the user experiencing Leptospirosis disease with severe symptoms of 37%. Naïve Bayes is able to diagnose with 100% accuracy seen from the total severe and mild symptoms